Keseimbangan Targhīb–Tarhīb dalam Hadis Nabi untuk Pembinaan Remaja Muslim pada Era Digital - Nabiilatus Tsaniah; Muhammad Ilyas (LP2M Universitas Islam Ahmad Dahlan, 2026)
The challenges of the digital age call for an approach to Islamic education that can balance the spiritual motivation and moral self-control of Muslim adolescents. This study aims to analyze the concepts of targhīb and tarhīb in the Prophet’s hadiths and their relevance as a conceptual foundation for fostering the moral character of Muslim adolescents in the digital age. The study employs a qualitative approach using a narrative literature review through documentary analysis and content analysis of targhīb–tarhīb hadiths from the Kutub al-Sittah and Musnad Ahmad. The analysis focuses on twelve hadiths selected through purposive sampling based on their relevance to adolescent moral education, the elements of targhīb–tarhīb, the context of the digital age, and the hadith’s authenticity (classified as ṣaḥīḥ and ḥasan). The study is supported by hadith commentaries, Islamic educational literature, adolescent developmental psychology, and research on digital moral challenges. The results indicate that targhīb–tarhīb hadiths embody Islamic educational principles that balance hope and fear proportionally. The analysis yielded four main educational themes: spiritual motivation and personal worship; the development of social character and empathy; moral discipline and social responsibility; and integrity and honesty. This study affirms that the balance of targhīb–tarhīb holds normative and pedagogical relevance as a conceptual framework for the moral development of Muslim adolescents in the digital age.